Somatisation: illness perspectives of asylum seeker and refugee patients from the former country of Yugoslavia - Hudelson Patricia; Junod Perron Noelle (BMC Family Practice, 2006)
Abstract Background Somatisation is particularly challenging in multicultural contexts where patients and physicians often differ in terms of their illness-related beliefs and practices and health care expectations. This paper reports on a exploratory study aimed at better understanding how asylum seeker and refugee patients from the former country of Yugoslavia who were identified by their physicians as somatising make sense of their suffering. Methods We conducted semi-structured interviews with 26 asylum seeker and refugee patients from the former country of Yugoslavia who attended the general medicine outpatient clinic of a Swiss teaching Hospital and were identified as presenting with somatisation. Interviews explored patients' illness perspectives and health care expectations. Interviews were audio taped, transcribed verbatim and analyzed to identify key themes in patients' narratives. Results Patients attributed the onset of symptoms to past traumatic experiences and tended to attribute their persistence to current living conditions and uncertain legal status. Patients formulated their suffering in both medical and social/legal terms, and sought help from physicians for both types of problems. Conclusion Awareness of how asylum seeker and refugee patients make sense of their suffering can help physicians to better understand patients' expectations of the clinical encounter, and the particular nature and constraints of the patient-provider relationship in the context of asylum.